2020
DOI: 10.1007/s11218-020-09556-0
|View full text |Cite
|
Sign up to set email alerts
|

Tests and academic cheating: do learning tasks influence cheating by way of negative evaluations?

Abstract: Desirable difficulties like tests were often shown to increase long-term learning. However, due to the complexity and difficulty of such tasks, they are also argued to result in negative consequences like stress, anxiety, pressure, frustration, or negative evaluations. In other studies, such consequences were, in turn, often found to increase dishonest behaviour. Hence, the present work tests the assumptions that tests as difficult learning tasks, contrary to reading, lead to more negative evaluations of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 95 publications
1
19
0
Order By: Relevance
“…A phenomenon like cheating raises the question as to the true extent of learning and its direct implications for a subsequently sustainable professional life [37] in terms of knowledge and unethical behavior. Studies have shown that Academic Dishonesty related behavior has intensified [20], as at some point of their careers, students engage in it [15,41]. This poses a significant ethical and educational problem that undermines the academic system's integrity, reputation [2], and sustainability, for these are built on the notions of trust in the knowledge produced and shared [42].…”
Section: Academic Dishonestymentioning
confidence: 99%
See 3 more Smart Citations
“…A phenomenon like cheating raises the question as to the true extent of learning and its direct implications for a subsequently sustainable professional life [37] in terms of knowledge and unethical behavior. Studies have shown that Academic Dishonesty related behavior has intensified [20], as at some point of their careers, students engage in it [15,41]. This poses a significant ethical and educational problem that undermines the academic system's integrity, reputation [2], and sustainability, for these are built on the notions of trust in the knowledge produced and shared [42].…”
Section: Academic Dishonestymentioning
confidence: 99%
“…Academic Dishonesty can be traced back to different personal and societal factors [15,20,41]. Whereas there is enough scholarly knowledge on the prevalence, nature, and consequences of Academic Dishonesty, relatively little is known about its connection to Statistics Anxiety, including the fact that a person's behavior is determined by their circumstances [43].…”
Section: Academic Dishonestymentioning
confidence: 99%
See 2 more Smart Citations
“…As stated, we do not have a complete understanding of why students cheat, or why business students cheat more often than other students, however, a proposed mechanism is that of justification (McCabe et al, 1993 ; Stone et al, 2009 ; Wenzel & Reinhard, 2020 ). Justification should enable students to cheat without experiencing dissonance – they justify their behavior by reframing it as something other than cheating.…”
Section: Introductionmentioning
confidence: 99%